Materializing low-cost energy-efficient residential utility through effective space design and masonry technique-a practical approach - Bukhari, H. (Horizon Research Publishing, 2021)
The swiftly mounting world energy consumption has sparked questions regarding supply constraints, the collapse of energy resources, and dense environmental effects. Although the construction industry has much developed, yet construction is still a difficult, and costly process. Consequently, there is a necessity to find additional energy-efficient and cost-saving substitutes to sustain the urbanization of houses at a reasonable price to low-income groups. This study aims to provide an energy-efficient proposal for a housing scheme with strict control over cost allowing the low-income groups to enjoy livability stemming from the thermally comfortable and cost-saving technology. For this purpose, visits and surveys were carried out to critically analyze the respective housing scheme. Two proposals were suggested i.e. Proposal A by applying a low-cost technique called a Rat-trap bond to the walls and Proposal B, by designing an architectural plan for proficient utilization of space along with Rat-trap bond. Proposal B is highly recommended for construction as it saves 799 units of electricity and is 28 cost-effective during the construction phase than the existing housing unit. Summarized results were prepared from cost analysis and Ecotect analysis which ascertains the proposal to be energy efficient in addition to low cost. It is recommended to invest in cost-effective and energy-efficient technologies at the governmental level so that the challenge of inadequate housing can be answered once and for all. Â© 2021 by authors, all rights reserved.